The Spatiotemporal Analysis of Dengue Fever in Purwosari District, Gunungkidul Regency, Indonesia - Indra Agus Riyanto; Noor Alia Susianti; Ratri Abdatush Sholihah; Raden Ludhang Pradipta Rizki; Ahmad Cahyadi; Muhammad Naufal; Fajri Ramadhan; Victor Kusuma Ramadan; Awanda Sistia Risky (Faculty of Geography, Universitas Gadjah Mada, 2020)
From 2014 to 2016, the number of prevalence of Dengue Hemorrhagic Fever (DHF) and deaths associated with DHF in Indonesia increased. DHF fatal cases were also reported from three administrative units in the Special Region of Yogyakarta, namely Bantul Regency, Gunungkidul Regency, and Yogyakarta City. Two related deaths in Purwosari, a district in Gunungkidul, raised the status of DHF to an outbreak. This study was designed to characterize the spread pattern of DHF in its endemic areas in Purwosari District using the retrospective method, anamnesis, in-depth interviews, Geographic Information System (GIS), and environmental analysis. The kernel density estimation revealed that in 2011-2017, DHF was concentrated in four villages, namely Giriasih, Giricahyo, Giritirto, and Giripurwo. There was a correlation between DHF incidents and physical geographical features of these villages, including proximity to water sources, high vegetation density, elevation, humidity, and rainfall, which created habitats for mosquito growth. A high incidence of DHF has been observed in children (50.8%) and students (57.4%), with most cases (78.7%) showing typical symptoms of the disease. A few of the 61 cases in the district developed into dengue shock syndrome (DSS) and led to death (4.9%), mainly because the public was unable to recognize the warning signs of DHF early and had limited knowledge of required management therapy. Moreover, the preventive or precautionary measures known as the 3M-Plus were not fully implemented yet.